(untitled) - Wilson, Warren (Hong Kong, 2007)
Fifty - fifty is the three level course in communicative English that provides speaking and listening practice for students from the elementary level through the intermediate level. This book is suitable for students at the intermediate level
Keywords: English language,English language,English language,Tiếng Anh,Tiếng Anh,Tiếng Anh; Textbooks for foreign speakers.,Sound recordings for foreign speakers,Spoken English,Sách giáo khoa dành cho người nước ngoài,Sự ghi âm dành cho người nước ngoài,Tiếng Anh giao tiếp